Halal Certification In International Trade - Kartika; Nasrullah Bin Sapa; Cut Muthiadin (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study aims to analyze the importance of halal certification in international trade and its impact on product competitiveness in the global market. The method used is a descriptive qualitative approach with a literature study, which collects secondary data from various scientific journals, reports, and regulations related to halal certification. The results of the study indicate that halal certification not only functions as a guarantee of compliance with Islamic teachings, but also as an effective marketing tool that can increase product competitiveness in the international market. In addition, countries with strong halal certification systems, such as Malaysia and Saudi Arabia, have an advantage in expanding their market access, while other countries need to improve the quality and credibility of their halal certification systems to compete in an increasingly competitive global market.